Direct Current Annealing Modulated Ordered Structure to Optimize Tensile Mechanical Properties of Co-Based Amorphous Metallic Microwires - Congliang Wang; Guanyu Cao; Jingshun Liu; Yun Zhang; Rui Liu; Feng Wang; Mingwei Zhang; Lu Wang; Bo Zhang (Metals, 2022)
Herein, the ordered structure of Co-based metallic microwires was modulated by direct current-annealing, thereby improving the tensile mechanical properties. Based on the thermophysical parameters of the metallic microwires, the annealing current intensities of 65 mA, 90 mA and 150 mA were determined by the method of numerical calculation. The experimental results indicated that the ordered structure of the metallic microwires was regulated under the action of Joule heating, and with the rising of the annealing current, the ordered structure increased and the distribution tended to be concentrated. The 90 mA current-annealed metallic microwires have favorable tensile mechanical properties and fracture reliability, with the tensile strength and elongation of 4540.10 MPa and 2.99%, respectively, and the fracture threshold is 1910.90 MPa. Both the as-cast and current-annealed metallic microwires were brittle fractures, and the fractures consisted of shear deformation regions and crack extension regions. The improvement of the mechanical properties of metallic microwires is related to the nano-ordered structure and their distribution. Under the condition of 90 mA current annealing, the uniformly distributed nano-ordered structures were formed in the amorphous matrix of the metallic microwires, which can effectively slow down the expansion of the shear bands and reduce the possibility of crack generation. This study provides process reference and theoretical guidance for the application of Co-based metallic microwires in the field of stress sensors.